Analysis of the Discipline Factors of Employees at the Sony Sugema College Surabaya Tutoring Institute - Tria Afsyari; Hermien Tridayanti (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2018)
Human resources are the most important resource for each company because every individual person as human resources have talent or ability, energy and creativity that is needed by the company to achieve every goals that planned by the company. To achieve these goals, theres a lot of factors that relate to improve the performances, one of them is discipline. This study analyzes the factors that influence employee discipline at the Sony Sugema College Surabaya Tutoring Institute with a population of 106 respondents and the sample known by the Slovin formula is 84 respondents. The results of factor analysis using SPSS 20 form 9 disciplinary factors of 28 indicators consisting of punishment sanction factor, exemplary leadership factor, remuneration factor, human relations factor, fairness factor, firmness factor, objectives and ability factor, work moral factor and waskat factor (supervision attached).